Pandemi Covid 19 Menambah Tantangan Pariwisata Pendakian Gunung Leuser - Ruanda, Romi; Mutiarin, Dyah; Damanik, Janianton (Jurnal Ilmiah Pariwisata, 2022)
This study aims to analyze the challenges of tourism in Gunung Leuser on Climbing as a tourism place faced both before and during the COVID-19 pandemic by collecting qualitative data sources such as interviews and direct observations and using the Nvivo application in analyzing tourism during the pandemic. Mount Leuser climbing tour at the Kedah resort which is next to the village of Kedah is the longest hiking trail in Indonesia. This research generally uses descriptive qualitative analysis techniques, the data presented here are in the form of statements that indicate the nature, characteristics and circumstances of the symptoms or events studied. This study uses the NVIVO analysis technique where the data used is secondary data derived from journal articles and government policies in handling COVID-19 in the Gunung Leuser area. The results showed that climbing Mount Leuser tourism was oriented towards special interest tourism and only certain groups of tourists tended to come to visit. The impact of COVID-19 on climbing tourism in Gunung Leuser also affects the Tourism Impact indicators (36%), International Law Travel (12), Travel Restrictions (24%), Tourism Policy (12%), Economy Recovery (4%), and Social Impact (4%). The percentage during Covid-19 that affects tourism policy (policy), affects the impact (recovery) of tourism in Gunung Leuser. Keywords: Leuser Tourism, Challenges, Covid 19, Kedah